Group medical Takaful for Universiti Utara Malaysia (UUM) staff in 2011 - Lim, Chee Chee; Ahmad, Shahrul Nizam (Emerald Group Publishing Limited, 2015)
Subject area– Human resource management; Employee benefits management.Study level/applicability – It can be used at undergraduate or postgraduate level for students at institutions of higher learning taking courses related to employee benefits management or human resource management. Case overview– The case is about the intention of Universiti Utara Malaysia (UUM) in purchasing health insurance for its employees in early 2011. For this purpose, a tender for group medical Takaful for UUM staff was placed in two major Malaysian newspapers on 20 February 2011. Then, after the tender closing date, a report was prepared and sent to the bursar of UUM, En Amron, on 28 April 2011.Ten companies had submitted their tenders; thus, En Amron had to identify the optimal group medical Takaful offered by the tenderers, so that he could put forward his recommendation to UUM tender committee board for its consideration and approval before the matter was brought to higher authorities for endorsement and implementation.Expected learning outcomes – This teaching case will enable students to explain the reasons why an employer provides health insurance, to evaluate the advantages and disadvantages of providing health insurance programme as non-contributory and contributory plans, to conduct company and plan assessment in making decision to purchase group medical Takaful and to evaluate either to purchase group health insurance directly from life insurer or to engage insurance broker.Supplementary materials – Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes.